Kajian Konseptual Identifikasi Pengaruh Iklim Kerja dan Budaya Organisasi terhadap Kinerja Guru - Handayani Handayani; Muhammad Win Afgani; Afriantoni Afriantoni (Journal on Education, 2024)
This study aims to identify the influence of work climate and organizational culture on teacher performance. Using a literature review method, this research gathers data from various books, journals, and related publications to analyze the theoretical relationship between these variables. The findings indicate that a conducive work climate and strong organizational culture can significantly enhance teacher performance. These results are supported by previous studies that show a positive correlation between work climate, organizational culture, and teacher performance. In conclusion, to improve teacher performance, schools need to create a supportive work environment and foster a positive organizational culture.